The Prognostic Significance of Anisomycin-Activated Phospho-c-Jun NH2-Terminal Kinase (p-JNK) in Predicting Breast Cancer Patients’ Survival Time - Chen, Li; Zhou, Xuantong; Kong, Xiangyi; Su, Zhaohui; Wang, Xiangyu; Li, Sen; Luo, Aiping; Liu, Zhihua; Fang, Yi; Wang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Phospho-c-Jun NH2-terminal kinase (p-JNK) and its downstream effector STAT3 are crucial breast cancer treatment. However, little is known about p-JNK’s role in shaping patients’ survival time. To bridge this gap, this study aims to investigate the prognostic significance of p-JNK in breast cancer patients receiving neoadjuvant chemotherapy (NACT) and analyze the relationship between anisomycin, p-JNK, phosphorylated signal transducer, and activator of transcription 3 (p-STAT3). A total of 104 breast cancer patients had NACT were enrolled in this study. The western blot and immunohistochemistry assays were used to determine the protein expressions of p-JNK and p-STAT3 in human breast cancer cell lines and patients’ cancer tissues, respectively. The chi-square test and Fisher’s exact test were adopted to gauge the associations between breast cancer and clinicopathological variables by p-JNK expression, whereas the univariate and multivariate Cox proportional hazards regression models were used to analyze the prognostic value of p-JNK expression. The Kaplan-Meier plots and the log-rank test were adopted to determine patients’ disease-free survival (DFS) and overall survival (OS). Findings indicated that the p-JNK expression had prognostic significance in univariate and multivariate Cox regression survival analyses. Results of log-rank methods showed that: (1) the mean DFS and OS times in patients with high p-JNK expression were significantly longer than those in patients with low p-JNK expression (χ2=5.908, P=0.015 and χ2=6.593, P=0.010, respectively), (2) the mean DFS and OS times in patients with low p-STAT3 expression were significantly longer than those in patients with high p-STAT3 expression (χ2=5.891, P=0.015 and χ2=7.014, P=0.008, respectively), and (3) the mean DFS and OS times in patients with low p-STAT3 and high p-JNK expression were significantly longer than those in patients with high p-STAT3 and low p-JNK expression (χ2=10.890, P=0.012 and χ2=11.530, P=0.009, respectively). p-JNK expression is a significant prognostic factor that can effectively predict the survival in breast cancer patients receiving NACT. Treatment with the JNK agonist anisomycin can induce apoptosis, lead to increased p-JNK expression and decreased p-STAT3 expression. Moreover, the p-JNK expression was inversely correlated with p-STAT3 expression. Patients with high p-JNK and low p-STAT3 expression had better prognosis.